Optimization design of fertilizer apparatus owned arc gears based on discrete element method - Dun, Guoqiang; Gao, Zhiyong; Liu, Yuxuan; Ji, Wenyi; Mao, Ning; Wu, Xingpeng; Liu, Wenhui (International Journal of Agricultural and Biological Engineering, 2021)
To improve the uniformity of the flow when fertilizer apparatus discharges fertilizer, a kind of fertilizer apparatus owned arc gears was designed. Also, the design and working principle of its general structure and key components were analyzed theoretically. Aiming at exploring the influence of arc structural parameters to the performance of arc gears discharging fertilizer, DEM simulation was used in this study. Fertilizer apparatus owned arc gears was taken as the research object to analyze the influence of two key components including the arc radius of gears’ concave-grooves and the minimal length between two mutual meshing gears. The variation coefficient of fertilizer discharging amount stability and the linear determined coefficient of fertilizer discharging amount in unit time as evaluation index were selected. Two factors and five levels quadratic rotation orthogonal experiment was applied, and Design-Expert 8.0 software was used to achieve data processing and analysis. The results of experiment indicated that the arc radius of gears’ concave-grooves had significant effect on the linear determined coefficient of fertilizer discharging amount in unit time, and the minimal length between two mutual meshing gears had significant effect on the variation coefficient of fertilizer discharging amount stability. The optimum structural parameters were 8.54 mm as the arc radius of gears’ concave-grooves and 5.22 mm as the minimal length between two mutual meshing gears. Upon this circumstance, the variation coefficient was 0.28 and determination coefficient was 0.9972. The optimum apparatus was selected to conduct the bench test and field simulation test. The results indicated that the variation coefficient is 0.27, and the linear determined coefficient of is 0.9980. The results of simulation experiment were anastomotic basically with the real result, which showed that DEM simulation technology was usable to the experiment of testing fertilizer discharging. The results of this research can provide a reference to the improving of performance in discharging fertilizer.Keywords: agricultural machinery, fertilizer apparatus, discrete element method, experiment, structure parameter, fertilizing performanceDOI: 10.25165/j.ijabe.20211402.5719Citation: Dun G Q, Gao Z Y, Liu Y X, Ji W Y, Mao N, Wu X P, et al. Optimization design of fertilizer apparatus owned arc gears based on discrete element method. Int J Agric & Biol Eng, 2021; 14(2): 97–105.